Tertiary Education Trust Fund’s Intervention In The Training And Development Of Academics In Nigerian Public Universities - Simon, Obadahun Oluwatoyin (2024)
Public universities in Nigeria are confronted with a mirage of challenges which include: a shortage of qualified academics, low research output, poor global ranking and unaccredited academic programmes, et cetera. Therefore, TETFund intervention in the training and development of academics of public universities through study fellowship, sponsorship of conference attendance and institutional-based research became imperative, given the New Public Management (NPM) that emphasises effectiveness, efficiency and economy. The main objective of this research is to assess the contribution of TETFund’s intervention in the training and development of academics at public universities in Nigeria. The institutional theory that emphasises isomorphism and a balanced scorecard model of performance measurement guided the research. The mixed-methods approach affords the use of both quantitative (questionnaire) and qualitative (interview) means of data collection simultaneously, and subsequently allows integration while discussing the finding through triangulation. Multiple regression analysis was used as statistical tools of analysis with the help of Statistical Package for Social Sciences software while the Nvivo 12 software was used to analyse the interview data obtained. The result revealed that there is a positive outcome as a result of the intervention which includes an increased number of qualified academics and improved global ranking. It also highlighted the inhibiting factors to the performance of the contribution of the intervention. The study recommended among other things that electronic means of communication be deployed in a complementary manner to the usual means (hard copies) so that documents that need to be submitted are done electronically to ensure that delays of submission are reduced to the barest minimum while approval and release of funds happen promptly. It concludes that TETFund intervention has contributed positively to the training and development of university academics. However, there is room for improvement to enhance better service delivery in Nigerian public universities.